Use of Reading Strategies in Anxiety Reduction Reading News Texts Class VII Students of SMP Negeri 1 Bantur - Ramadhani, Putri; Prihatini, Arti; Andalas, Eggy Fajar (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Reading is a competency that needs to be possessed in Indonesian learning which includes reading news texts. In reading news texts, students need to have a reading strategy to understand the text read. The purpose of this study is to determine the use of reading strategies in overcoming reading anxiety in Indonesian learning, especially in reading a news text in grade VII students at SMP Negeri 1 Bantur. The method used in this finding is qualitative using the case study method. The data collection uses qualitative and quantitative means. Quantitative data collection is carried out by distributing questionnaires with instruments proposed by Sheorey & Mokhtari to 47 grade VII students of SMP Negeri 1 Bantur. The accumulation of qualitative data is carried out using interviews and direct observation. The findings revealed that the overall level of use of reading strategies in news texts was moderate with an average of 2.94. The highest level of use of news text reading strategies is reading strategies Problem Solving (PROB) with an average of 4.13. Furthermore, the global problem reading strategy (GLOB) with an average of 2.88, and the support reading strategy (SUPP) with an average of 2.64. Thus, it can be concluded that in the news text material, grade VII students at SMP Negeri 1 Bantur are users of reading strategies and problem-solving.